2014
DOI: 10.1681/asn.2013121343
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Arrhythmias in a Model of CKD

Abstract: Patients with CKD have an increased risk of cardiovascular mortality from arrhythmias and sudden cardiac death. We used a rat model of CKD (Cy/+) to study potential mechanisms of increased ventricular arrhythmias. Rats with CKD showed normal ejection fraction but hypertrophic myocardium. Premature ventricular complexes occurred more frequently in CKD rats than normal rats (42% versus 11%, P=0.18). By optical mapping techniques, action potential duration (APD) at 80% of repolarization was longer in CKD rats (78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 47 publications
7
50
5
2
Order By: Relevance
“…It seems therefore that conduction slowing is not a prerequisite for arrhythmias in this model. Triggered activity as an arrhythmia mechanism was shown earlier in a chronic kidney disease rat model [27]. This is well supported by the high-resolution epicardial activation mapping in our study, which did not show evident signs of reentry, making a triggered activity a very likely mechanism for the arrhythmias.…”
Section: Discussionsupporting
confidence: 90%
“…It seems therefore that conduction slowing is not a prerequisite for arrhythmias in this model. Triggered activity as an arrhythmia mechanism was shown earlier in a chronic kidney disease rat model [27]. This is well supported by the high-resolution epicardial activation mapping in our study, which did not show evident signs of reentry, making a triggered activity a very likely mechanism for the arrhythmias.…”
Section: Discussionsupporting
confidence: 90%
“…At the cellular level, the cardiac sodium channel, the potassium channel, and calcium handling are abnormal in CKD rats, leading to increased vulnerability to early after depolarization and ventricular arrhythmias. 30) Inherited factors are also considered to be a risk factor for SCD among CKD patients. 31) Based on the reasons explained above, we were not surprised to obtain this result in stage 3 CKD patients.…”
Section: Icds Reduce Mortality In Patients With Ckdmentioning
confidence: 99%
“…Our previous study 8 found abnormal ion channel function and calcium handling in the CKD rats. These changes may play a role in producing sinus bradycardia and AV block.…”
Section: Discussionmentioning
confidence: 88%
“…Cardiac ion channel and calcium handling are abnormal in these CKD rats. 8 These abnormalities may increase ventricular arrhythmogenesis and result in SCD. However, the terminal arrhythmia causing SCD remains unclear.…”
mentioning
confidence: 99%